The Effect of Enterprise Multiple, Economic Profit Ratio, and Capex to Revenue Ratio on Company Stock Prices in Indonesia - chaerul anwar, wawan (Management Research Studies Journal, 2025)
Abstract-This study aims to analyze the influence of the Enterprise Multiple ratio value on the same price, analyze the influence of investment decisions using Economic Profit Ratio and Capex to Revenue Ratio on stock prices, and determine whether the results of the research can be used as a tool to measure the feasibility of investments that have been made by PT Telkom Indonesia (Persero) Tbk. This study uses a multiple linear regression analysis method with an auto model Regression to identify the influence of the three independent variables on the company's stock price, using historical data from the company's financial statements and stock price. The results show that, partially, there is no significant influence of Enterprise Multiple, Economic Profit Ratio, and Capex to Revenue Ratio on the company's stock price. This finding provides practical implications for investors and financial analysts to consider stock price factors in the previous period in forecasting future stock price movements.